PERFORMANCE ANALYSIS OF FIELD AGRICULTURAL EXTENSION WORKERS IN KARO REGENCY - Ripka Prianti Ginting; Rahmanta; Salmiah; Terkelin Surbakti (RADJA PUBLIKA, 2024)
Agricultural extension as a system of empowering farmers is a non-formal education system for farming families that aims to assist farmers in improving technical skills, knowledge, developing more positive attitude changes and building independence in managing their agricultural land. The performance of an agricultural extension agent reflects his abilities and skills in carrying out the tasks he is assigned. This study aims to analyze how the performance of Field Agricultural Extension and analyze the factors that influence the performance of Field Agricultural Extension in Karo District. The analytical model used in this research is using descriptive analysis and scoring by calculating the Work Performance Value (NPK) from the Independent Evaluation Score of each extension worker to see the work performance value of the instructor and multiple linear regression analysis to see the factors that affect performance agricultural field extension in Karo District. The data used is primary data collected through direct interviews using questionnaires to selected respondents. The results showed that the work performance value (NPK) of Field Agricultural Extension (PPL) in Karo Regency was 76.14 in the good category. Factors of age, formal education, training, the number of assisted villages, the number of assisted groups have a positive and significant effect on the performance of field agricultural extension agents in Karo District, while the distance to the work area has a negative and significant effect on the performance of field agricultural extension agents in Karo District. Variable length of service has no significant and significant effect on the performance of agricultural extension workers.